الذكاء الوجداني و علاقته بالتوافق الدراسي لدى عينة من الطلبة الجامعيين دراسة ميدانية لدى عينة من طلبة في جامعة عمار ثليجي الاغواط - حميدات فاطمة; شاوي مرية; داودي محمد (My University, 2023)
This study aimed to identify the relationship between emotional intelligence and academic adaptation of the university student, and the main sample consisted of 50 male and female students. After statistical treatment, the study yielded the following results: The level of emotional intelligence among the study sample is high. - The level of academic adaptation among the study sample is high. - There is a direct correlation between emotional intelligence and school adjustment among the sample. - There are statistically significant differences between male and female students in the degrees of emotional intelligence and therefore, it can be said that there are differences due to the gender variable in emotional intelligence. - There are no statistically significant differences between men and women in the school adjustment variable, and it can therefore be said that there are no differences attributable to the sex variable in the school adjustment . keywords: - Emotional intelligence - Academic adaptation